Developmental Expression Pattern of the Cholesterogenic Enzyme NSDHL and Negative Selection of NSDHL-deficient Cells in the Heterozygous Bpa(1H)/+ Mouse - Cunningham, David (2009)
NSDHL (NAD(P)H sterol dehydrogenase-like), is a 3β-hydroxysterol dehydrogenase thought to function in the demethylation of sterol precursors in one of the later steps of cholesterol biosynthesis. Mutations in the X-linked NSDHL gene cause CHILD syndrome in humans, and the male-lethal bare patches (Bpa) phenotype in mice. The relative level of NSDHL expression among different mouse tissues at several stages of embryogenesis and postnatal development was analyzed by immunohistochemistry. In wild type (WT) embryos, the highest levels of expression were seen in the liver, dorsal root ganglia, central nervous system, retina, adrenal gland and testis. Heterozygous Bpa(1H) females are mosaic for NSDHL expression due to normal random X inactivation. NSDHL deficient cells were detected in the developing cerebral cortex and retina of Bpa(1H) female embryos. In postnatal WT and Bpa(1H) animals, we compared the expression pattern of NSDHL in skin, an affected tissue; liver, a main site of cholesterol synthesis; and brain, a tissue dependent on endogenous synthesis of cholesterol due to lack of transport across the blood-brain barrier. Clonal populations of mutant cells were visible in the brain, skin and liver of Bpa(1H) pups. In the liver, the proportion of NSDHL negative cells dropped from ~50% at postnatal day 6 to ~20% at one year of age. In the brain, which showed the highest expression in cerebral cortical and hippocampal neurons, the proportion of NSDHL negative cells also dropped dramatically over the first year of life. Our results suggest that while NSDHL deficient cells in the mosaic Bpa(1H) female are able to survive and differentiate during embryonic development, they are subject to negative selection over the life of the animal.